Odpowiedzi

2010-01-25T15:59:51+01:00
A) (2-5)x2=(-3)x2=(-6)
b) 5-16=(-11)
e) 27+2=29
f) 3-4= (-1)
g) 4:4=1
h) (2+3)x9=5x9=45
1 5 1
2010-01-25T16:00:13+01:00
A) (³√8-√25)×2= (2 -5)*2 = (-3)*2 = -6
b) √5²-4²= 5 - 16 = -11
e) 3³+√4= 27 + 2 = 29
f) ³√27-(-2)²= 3 - 4 = -1
g) √16:(-2)²= 4 : 4 = 1
h) (³√8+√9)×(-3)²= (2 + 3)*9= 5*9 = 45
1 5 1
2010-01-25T16:02:39+01:00
A) (³√8-√25)×2= (2 - 5)x2 = -3x2 = -6
b) √5²-4²= 5 - 16 = - 11
e) 3³+√4= 27 + 2 = 29
f) ³√27-(-2)²= 3 - 4 = - 1
g) √16:(-2)²= 4/4 = 1
h) (³√8+√9)×(-3)²= (2 + 3)x9 = 5 x 9 = 45


1 5 1